Islamic Ethical Investment as Mechanism to Mitigate Agency Conflict: An Empirical Study in Indonesian Stock Exchange - Hanafi, Syafiq M. (Al-Jamiah Research Centre, 2013)
This paper attempts to investigate whether Ethical Investment (EI) could reduce the role of dividend and debt in reducing agency conflict between controlling and public shareholders in Indonesia. I investigate market reaction when EI and Non-EI stocks announce dividend payments, dividend non-payments, and bond issuance. I also investigate the effect of EI and the interaction between EI and dividend and between EI and debt on companyâs value. The smaller market reaction shows that EI stocks contain less surprise, since EI stocks are able to reduce information asymmetry, and increase trust among investors. The empirical results show that market reaction for debt issuance is less positive for EI stocks than for Non-EI stocks. Regression analysis shows that EI strengthens the role of debt in increasing companyâs value. The role of EI in reducing agency conflict seems to have multi-dimensions. Event studies show that debt could be used as a substitute for debt in reducing agency conflict, but regression result shows that EI complements debt in reducing agency conflicts, and increases companyâs value. Overall I conclude that EI provide an important role as mechanisms to reduce agency conflict, and increase companyâs value.[Artikel ini menelisik apakah Ethical Investment (EI) dapat mengurangi peran dividen dan bunga dalam menekan konflik perusahaan antara manajer dan pemilik saham publik di Indonesia. Reaksi pasar akan dilihat ketika stok EI dan non-EI mengumumkan dividen dibayarkan, dividen tidak dibayarkan, dan bon pengeluaran. Hal lain yang juga dilihat adalah pengaruh dari EI dan interaksi antara EI dan dividen serta antara EI dan hutang pada nilai perusahaan. Reaksi pasar yang lebih kecil menunjukkan bahwa stok EI tidak banyak mengejutkan, karena stok EI dapat mengurangi ketidaksinkronan informasi sekaligus meningkatkan kepercayaan investor. Analisis lapangan menunjukkan bahwa pengumuman tentang hutang perusahaan memiliki dampak kurang positif pada stok EI daripada non- EI. Sedangkan analisis regresi menunjukkan bahwa EI memperkuat peran hutang dalam meningkatkan nilai perusahaan. Sementara itu, peran EI dalam menekan konflik perusahaan tampak memiliki banyak dimensi. Secara umum dapat disimpulkan pula bahwa EI memiliki peran yang cukup penting dalam mekanisme untuk menekan agency conflict dan meningkatkan nilai perusahaan.]